The Effect of Current Density and Hard Chrome Coating Duration on the Mechanical and Tribological Properties of AISI D2 Steel - Hasanah, Indah Uswatun; Priadi, Dedi; Dhaneswara, Donanta (UI Scholars Hub, 2023)
The effect of hard chromium coating on AISI D2's mechanical properties and wear resistance has been investigated using the electrolysis technique with varying current and coating duration. The variations of current used are 0.8 A, 1.2 A, and 1.6 A, while the coating duration used are 300, 600 and 900 seconds. Characterization of the films was conducted using SEM-EDS, and XRD. It can be observed from SEM characterization that the chrome grains resulted from the electroplating process are fine. The XRD identify chrome compund on the surface coating. The highest hardness value was 520.6 HV on a sample with a current of 1.6 A and a coating duration of 900 seconds and the lowest wear value was 2.85x10-6 mm3/mm on a sample with a current of 1.6 A and a coating duration of 900 seconds.